Effect of pressure on the Fermi surface and electronic structure of ErGa3 : Электpонные свойства металлов и сплавов - Grechnev, V. B. Pluzhnikov G. E.; Fomenko, Yu. V.; Czopnik, A.; Eriksson, O.; Grechnev, G. E.; Fomenko, Yu. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The Fermi surface and cyclotron masses of the ErGa3 compound are studied by means of the de Haas-van Alphen technique under pressure. Concurrently, the electronic structure is calculated ab initio for the ferromagnetic phase of ErGa3. The experimental data have been analyzed on the basis of the calculated volume-dependent band structure and compared with available results for isostructural TmGa3 and LuGa3 compounds.